Фітопатологічний стан рослин роду Tilia L. у насадженнях дендрологічного парку “Олександрія” - Masalsky, V.P. (M.M. Gryshko National Botanical Garden of the NAS of Ukraine, 2005)
The results of phytopathology inspection of limes plantation of the dendrological park Alexandria. To show up six fungoid disease, two species of lichens and mistletoe. Its are growing on difference morphology organs of genus. We offered the ways of struggle with its.